Cannabinoid receptor 1 gene and irritable bowel syndrome: phenotype and quantitative traits - Camilleri, Michael (American Physiological Society, 2013)
Genetic variations in metabolism of endocannabinoids and in CNR1 (gene for cannabinoid 1 receptor) are associated with symptom phenotype, colonic transit, and left colon motility in irritable bowel syndrome (IBS). Our aim was to evaluate associations between two variations in CNR1 genotype (rs806378 and [AAT]n triplets) with symptom phenotype, small bowel and colonic transit, and rectal sensations in 455 patients with IBS and 228 healthy controls. Small bowel and colonic transit were measured by scintigraphy, rectal sensation by isobaric distensions. Associations with genotype were assessed by χ(2) test (symptom phenotype) and ANCOVA (quantitative traits) based on a dominant genetic model. Significant association of CNR1 rs806378 (but not CNR1 [AAT]n) genotype and symptom phenotype was observed (χ(2) P = 0.028). There was significant association of CNR1 rs806378 (P = 0.014; CC vs. CT/TT) with colonic transit in IBS-diarrhea (IBS-D) group; the TT group had the fastest colonic transit at 24 and 48 h. There was significant overall association of CNR1 rs806378 with sensation rating of gas (P = 0.025), but not pain; the strongest associations for gas ratings were in IBS-D (P = 0.002) and IBS-alternating (P = 0.025) subgroups. For CNR1 (AAT)n, gene-by-phenotype interactions were observed for colonic transit at 24 (P = 0.06) and 48 h (P = 0.002) and gas (P = 0.046, highest for IBS-D, P = 0.034), but not pain sensation; the strongest association with transit was in controls, not in IBS. These data support the hypothesis that cannabinoid receptors may play a role in control of colonic transit and sensation in humans and deserve further study as potential mediators or therapeutic targets in lower functional gastrointestinal disorders.